Understanding Factors Influencing Cycling Behaviour Among University Students and Staff: A Cross-Sectional Study - Isabel M. Martín-López; Olalla García-Taibo; Antoni Aguiló; Pere Antoni Borràs (Social Sciences)
Active commuting by bicycle offers health and environmental benefits, yet it remains uncommon among university populations. This study aimed to identify key factors influencing bicycle commuting among university students and staff based on cyclist typology and to assess the applicability of the Theory of Planned Behaviour (TPB) and socio-ecological models. A total of 305 students and 79 staff completed a questionnaire assessing sociodemographic, psychological, social, and environmental variables. Results revealed significant differences based on cyclist typology. Urban cyclists reported fewer perceived barriers (1.96 ± 0.59) and more advantages (3.61 ± 0.40) than non-cyclists (2.71 ± 0.56 and 3.26 ± 0.49, respectively; p < 0.001). While personal and psychological factors were most influential for non-cyclists, environmental aspects were more relevant for urban cyclists and cyclists. Multinomial logistic regression showed that for both cyclists and urban cyclists, bicycle ownership (OR = 0.098–0.104, p < 0.001) and intention to use (OR = 0.091–0.358, p ≤ 0.02) were key predictors of cycling behaviour. Although gender was only a significant predictor for cyclists (OR = 3.41, p = 0.003), this variable did not influence urban cycling behaviour. These findings support using TPB and socio-ecological models to design targeted, multilevel interventions.